Atypical Presentations and Specific Genotypes Are Associated With a Delay in Diagnosis in Females With Rett Syndrome - Fehr, S.; Downs, Jennepher; Bebbington, A.; Leonard, H. (John Wiley & Sons, Inc., 2010)
There is often delay between onset of Rett syndrome symptoms and its diagnosis, possibly related to symptom presentation or socio-demographic factors. We hypothesized that girls with an atypical presentation or whose family had a lower socio-economic status would receive a later diagnosis. Female subjects with a confirmed diagnosis of Rett syndrome were sourced from the Australian Rett Syndrome and InterRett Databases. Variables analyzed included timing and development of symptoms; MECP2 mutation type; parental occupation and education; maternal age and birth order. Residential location and socio-economic status were also analyzed for the Australian cases. Linear regression was used to determine relationships between these factors and age at diagnosis.A total of 909 cases were included. An older age of diagnosis was associated with later loss of hand function and speech, later onset of hand stereotypies and the presence of the p.R133C or p.R294X MECP2 mutation. Socio-economic factors did not predict age of diagnosis for Australian families. For families participating in the InterRett database, a younger age of diagnosis was associated with higher levels of parental education or occupation. A clinical picture consistent with the classic presentation of Rett syndrome is associated with an earlier diagnosis. Clinicians need to be alerted to the variable presentation of Rett syndrome including the milder phenotypes of cases with the p.R133C or p.R294X mutation. Educational resources to assist this understanding including guidance on when to request genetic testing could be useful to streamline the process of diagnosis in Rett syndrome.